2001
DOI: 10.1007/s004240100557
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic input to the supraoptic nucleus increases Fos expression and body temperature in rats

Abstract: To examine the role played by cholinergic input and processes in the supraoptic nucleus (SON) in the control of body temperature and water intake in rats, we used microdialysis to stimulate and analyze SON without disturbing the behavior of unanesthetized rats. After microdialysis, we also investigated immunoreactivity for c-Fos protein in the brain as an index of neuronal activation. Stimulation with neostigmine, an acetylcholine esterase inhibitor, through the microdialysis probe increased the extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…These neurotransmitters also regulate Fos expression in the developing and adult brain. That is, dopamine induces Fos expression in fetuses (57, 58) and neonates (17), and norepinephrine (59) and acetylcholine (60, 61) both induce Fos expression in adults, indicating that sex differences in these neurotransmitter systems may contribute to sex differences in Fos expression. Another possibility is that the sex differences in Fos expression may partially result from a sex difference in response to a particular transmitter.…”
Section: Discussionmentioning
confidence: 99%
“…These neurotransmitters also regulate Fos expression in the developing and adult brain. That is, dopamine induces Fos expression in fetuses (57, 58) and neonates (17), and norepinephrine (59) and acetylcholine (60, 61) both induce Fos expression in adults, indicating that sex differences in these neurotransmitter systems may contribute to sex differences in Fos expression. Another possibility is that the sex differences in Fos expression may partially result from a sex difference in response to a particular transmitter.…”
Section: Discussionmentioning
confidence: 99%
“…Several findings indicate that the SON participates in thermoregulatory events. Indeed, it has recently been suggested that thermal information from the preoptic area sends excitatory signals to the SON (Yoshida et al, 2002), that cholinergic inputs to the supraoptic nucleus increase Fos expression and body temperature in rats (Takahashi et al, 2001a), and that neurons located in the SON increase nonshivering thermogenesis in brown adipose tissue by activating sympathetic pathways (Takahashi et al, 2001b). Therefore, it seems rational to suggest that this type of heat-producing circuitry is inactive in animals undergoing an increase in body temperature due to exposure to a warm environment.…”
Section: 3mentioning
confidence: 99%